Rancang Bangun Aplikasi Analisis Kebutuhan Pelatihan Berbasis Kompetensi Pada PT. Geo Given Visi Mandiri - Ramadian Nurqolbi; Haryanto Tanuwijaya; Tony Soebijono (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
PT. Geo Given Visi Mandiri (PT. GGVM) is an innovative company that is engaged in the field of human resources services. PT. GGVM offer the provision of manpower to a sales force of the company. PT. GGVM has a vision to be the best as providers of employment services company to provide services and qualified human resources to the client.Training is one of the means to improve the competence of the workforce. At the PT. Geo Given Visi Mandiri, the training has not run optimally because the existing training planning is done without any training needs analysis in advance. This can result in a mismatch between the needs of competence in performing a job with competence possessed by today's workforce.Based on the results of the test and evaluation of training needs analysis application, indicating that the application can help PT. Geo Given Visi Mandiri in terms of manpower assessment, planning training needs, and provide reports in accordance with the company's needs.